High-performance work practices and organizational performance in Pakistan. Issue 3 (6th December 2019) - Ahmad, Mansoor; Raziq, Muhammad Mustafa; Rehman, Wali ur; Allen, Matthew M.C.
Abstract : Purpose: Research on the relationship between high-performance workplace practices (HPWPs) and organizational performance has largely focussed on western settings, limiting the knowledge of how these systems influence performance in other countries, including Pakistan. Universalistic assumptions underpin the HPWP paradigm; to examine the validity of these assumptions, the purpose of this paper is to study the links between HPWP and performance in Pakistan, a country with different cultural norms and institutional settings to those in which most research has been conducted. Design/methodology/approach: The authors draw on a unique survey of 392 establishment managers in the banking, pharmaceutical and information technology sectors. The authors include managers of foreign-owned multinational subsidiaries and domestic firms to ensure the sample represents firms in Pakistan. Findings: The authors find that some individual HPWPs (recruitment and training) are associated in a statistically significant way with lower labour turnover, higher productivity and higher financial performance. Employee involvement is associated with lower labour turnover and higher labour productivity. Compensation is associated with higher financial performance. None is linked to higher labour turnover, lower productivity or lower financial performance in a statistically significant way. Performance appraisal was not statistically significantly associated with any of the three outcome variables. Originality/value: The results provide some relatively strong support for universalistic assumptions, but also highlight the need for future research to examine the variable links of some HPWPs and the lack of any association for the performance appraisal measure.